114 Persistence of Haemoglobin Degradation Products within Infarct Scar Tissue after ST-elevation Myocardial Infarction: Incidence, Correlates and Implications for Left Ventricular Remodelling. (3rd June 2016) - Carberry, Jaclyn; Carrick, David; Haig, Caroline; Rauhalammi, Sam; Ahmed, Nadeem; Mordi, Ify; McEntegart, Margaret; Petrie, Mark; Eteiba, Hany; Hood, Stuart; Watkins, Stuart; Lindsay, Mitchell; et al.
Abstract : Background: Myocardial haemorrhage is a prognostically important complication of acute ST-elevation myocardial infarction (STEMI). Persistence of haemoglobin degradation products within infarct scar tissue and the potential clinical significance have not been investigated. Methods and Results: Patients who sustained an acute STEMI were enrolled in a cohort study (BHF MR-MI; ClinicalTrials.gov: NCT02072850 ). 211 patients (mean (SD) age 57 (11) years, 77% male) had evaluable T2* cardiac magnetic resonance (CMR) imaging (1.5 Tesla) 2 days 6 months post-MI. Myocardial haemorrhage was defined as a hypointense infarct core with T2* signal <20ms. At 2 days, 79 (37%) patients had evidence of myocardial haemorrhage. At 6 months, 47 (59%) patients had a hypointense infarct core and 32 (41%) did not. None of the patients had de novo haemorrhage after the first CMR scan. Clinical associates of a persistent hypointense core at 6 months included hypertension (odds ratio (95% confidence interval) 0.28 (0.08, 0.95); p = 0.040), heart rate (1.08 (1.03, 1.13); p = 0.001), systolic blood pressure (1.06 (1.01, 1.12); p = 0.015), neutrophil count (2.19 (1.01, 4.74); p = 0.048), left anterior descending as culprit artery (9.26 (1.26, 67.99); p = 0.029), infarct size (1.10 (1.03, 1.17); p = 0.004) and initial haemorrhage size (1.34 (1.06, 1.66); p = 0.012). A hypointense infarct core with T2*-mapping at 6 months was associated with worsening LV end-diastolic volume (regression coefficient (95% confidence interval) 15.43 (1.35, 29.50); p = 0.032) and worsening left ventricular ejection fraction (-4.15 (-7.40, -0.89); p = 0.013). Conclusion: Persistence of haemoglobin degradation products at 6 months post-STEMI is common and prognostically important.